Evaluating pharmacist intervention using the Simpler tool in Malaysian patients with Type 2 diabetes. - Ayadurai, S.; Sunderland, V.B.; Tee, Lisa; MD Said, S.N.; Hattingh, H.L. (2020)
Introduction: The validated Simpler tool encompasses seven targeted areas for diabetes care and their corresponding indicators to facilitate the delivery of structured, multifaceted interventions and provide consistent, quality type 2 diabetes mellitus (T2DM) care.